Synthesis of carbon/α-Al2O3 composite adsorbents for the elimination of methyl-ethyl ketone vapour - Kuśtrowski, P.; Molenda, M.; Janus, R.; Kochanowski, A.; Piwowarska, Z. (Polimery, 2010)
α-Al2O3 has been modified by the deposition of different amounts of polyacrylonitrile (PAN) via precipitation radical polymerization in an aqueous suspension. Carbonization of the product performed in an inert atmosphere at 350 °C resulted in obtaining of a carbon layer supported on the surface of α-Al2O3. The content of carbon in the composites was determined by temperature-programmed oxidation, whereas textural properties of the synthesized samples were studied by low-temperature sorption of N2 (BET). The carbon/α-Al2O3 composites appeared to be effective adsorbents of methyl ethyl ketone vapour.